Solid electrolyte material and battery using the same
By adopting solid electrolyte materials with specific composition and synthesis processes, the problems of high melting point and low conductivity of materials in the prior art are solved, low melting point and high lithium ion conductivity are achieved, and the performance and safety of the battery are improved.
Patent Information
- Application Number
- CN202080091413.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-01-29
- Filing Date
- 2020-12-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2040-12-09
AI Technical Summary
The prior art is difficult to provide solid electrolyte materials with low melting point and high lithium ion conductivity, which affects the charging and discharging characteristics and safety of the battery.
A solid electrolyte material composed of Li, Y, X, O and H, where X is F, Cl, Br or I, and the molar ratio of O to Y is between 0.01 and 0.38, and is subject to specific synthesis methods and process conditions. , a material with low melting point and high lithium ion conductivity was prepared.
The low melting point and high lithium ion conductivity of solid electrolyte materials are achieved, the charging and discharging characteristics and safety of the battery are improved, and the production of hydrogen sulfide is avoided.
Smart Images

Figure CN114945996B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a solid electrolyte material and a battery using the same. Background Art
[0002] Patent Document 1 discloses an all-solid-state battery using a sulfide solid electrolyte. Patent Document 2 discloses a solid electrolyte material represented by the compositional formula Li 6-3z Y z X 6 (where 0 < z < 2 and X is Cl or Br).
[0003] Prior Art Documents
[0004] Patent Documents
[0005] Patent Document 1: Japanese Patent Application Laid-Open No. 2011-129312
[0006] Patent Document 2: International Publication No. 2018 / 025582 Summary of the Invention
[0007] Problems to be Solved by the Invention
[0008] An object of the present disclosure is to provide a solid electrolyte material having a low melting point and a high lithium ion conductivity.
[0009] Means for Solving the Problems
[0010] The solid electrolyte material of the present disclosure is composed of Li, Y, X, O, and H, where X is one selected from F, Cl, Br, and I, and the molar ratio of O to Y is greater than 0.01 and less than 0.38.
[0011] Advantages of the Invention
[0012] The present disclosure provides a solid electrolyte material having a low melting point and a high lithium ion conductivity. Brief Description of the Drawings
[0013] Figure 1 A cross-sectional view showing the battery 1000 of the second embodiment.
[0014] Figure 2 A chart showing X-ray diffraction patterns of the solid electrolyte materials of Examples 1 to 3 and Comparative Examples 1 and 2.
[0015] Figure 3 A schematic view showing the compression molding die 300 used for evaluating the ionic conductivity of the solid electrolyte material.
[0016] Figure 4This is a graph showing a Cole-Cole plot of the impedance measurement results of the solid electrolyte material of Example 1.
[0017] Figure 5 This is a graph showing infrared absorption spectra of the solid electrolyte materials of Examples 1 to 3 and Comparative Examples 1 and 2.
[0018] Figure 6 This is a graph showing the results of thermal analysis of Examples 1 to 3 and Comparative Example 1.
[0019] Figure 7 This is a graph showing the initial discharge characteristics of the battery of Example 1. DETAILED DESCRIPTION
[0020] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.
[0021] (First embodiment)
[0022] The solid electrolyte material of the first embodiment is composed of Li, Y, X, O and H. X is one selected from F, Cl, Br and I. The molar ratio of O to Y is greater than 0.01 and less than 0.38. The solid electrolyte material of the first embodiment has a low melting point. Furthermore, the solid electrolyte material of the first embodiment has a high lithium ion conductivity. The so-called low melting point is, for example, 504°C or less. In the case where the solid electrolyte material is a multiphase material, the melting point of the solid electrolyte material refers to the highest temperature among the melting points of the solid electrolyte material. In addition, the so-called high lithium ion conductivity is, for example, 1×10 -4 S / cm or more. That is, the solid electrolyte material of the first embodiment may have, for example, a melting point of 504°C or less and a -4 S / cm or above ionic conductivity.
[0023] The solid electrolyte material of the first embodiment can be used to obtain an all-solid battery having excellent charge and discharge characteristics. The all-solid battery may be a primary battery or a secondary battery.
[0024] The solid electrolyte material of the first embodiment preferably does not contain sulfur. A solid electrolyte material that does not contain sulfur does not generate hydrogen sulfide even when exposed to the atmosphere, and therefore has excellent safety. The sulfide solid electrolyte disclosed in Patent Document 1 can generate hydrogen sulfide when exposed to the atmosphere.
[0025] The solid electrolyte material of the first embodiment may be composed of Li, Y, X, and O only.
[0026] In order to improve the ionic conductivity of the solid electrolyte material, the solid electrolyte material of the first embodiment may further include at least one selected from Mg, Ca, Zn, Sr, Ba, Al, Sc, Ga, Bi, La, Zr, Hf, Ta and Nb.
[0027] The transition metal contained in the solid electrolyte material of the present embodiment may be only Y, except for elements contained as inevitable impurities.
[0028] X may also be Cl. Such a solid electrolyte material has a low melting point and high ion conductivity.
[0029] In order to improve the ion conductivity of the solid electrolyte material, O bonded to H may exist in the surface region of the solid electrolyte material of the first embodiment.
[0030] Here, the surface region of the solid electrolyte material in the first embodiment refers to a region extending from the surface of the solid electrolyte material to a depth of about 1 μm in the inner direction.
[0031] The X-ray diffraction pattern of the solid electrolyte material of the first embodiment can be measured using Cu-Kα rays. In the obtained X-ray diffraction pattern, peaks may also exist within the range of diffraction angles 2θ of 15.2° to 16.3°, 17.4° to 18.5°, 30.8° to 31.9°, 33.1° to 34.2°, 40.3° to 41.4°, 48.1° to 49.3°, and 53.0° to 54.1°. Such a solid electrolyte material has a low melting point and high ionic conductivity.
[0032] In order to lower the melting point of the solid electrolyte material, the molar ratio of O to Y may be greater than 0.01 and not more than 0.21.
[0033] The shape of the solid electrolyte material of the first embodiment is not limited. Examples of the shape are needle-shaped, spherical, or ellipsoidal. The solid electrolyte material of the first embodiment may also be particles. The solid electrolyte material of the first embodiment may also be formed in a particle or plate shape.
[0034] When the shape of the solid electrolyte material of the first embodiment is a particle shape (for example, a spherical shape), the solid electrolyte material of the first embodiment may have a median particle size of 0.1 μm to 100 μm.
[0035] In order to improve the ionic conductivity of the solid electrolyte material of the first embodiment and to disperse the solid electrolyte material and active material of the first embodiment well, the solid electrolyte material of the first embodiment may also have a median particle size of 0.5 μm to 10 μm. In order to further disperse the solid electrolyte material and active material of the first embodiment well, the solid electrolyte material of the first embodiment may also have a smaller median particle size than the active material. The median particle size refers to the particle size when the cumulative volume in the volume-based particle size distribution is equal to 50%. The volume-based particle size distribution can be measured by a laser diffraction measuring device or an image analysis device.
[0036] <Method for producing solid electrolyte material>
[0037] The solid electrolyte material of the first embodiment can be produced by the following method.
[0038] First, a plurality of halides are mixed as raw material powders.
[0039] As an example, when a solid electrolyte material composed of Li, Y, Cl, O, and H is prepared, YCl 3 The raw material powder and the LiCl raw material powder are mixed. The obtained mixed powder is fired in an inert gas atmosphere (for example, an argon atmosphere with a dew point below -60°C) in which the oxygen concentration and the water concentration are adjusted. The firing temperature may be, for example, in the range of 200°C to 650°C. The obtained reaction product may be left to stand in an atmosphere with a relatively high dew point (for example, an argon atmosphere with a dew point of -30°C). In order to offset the composition changes that may occur in the synthesis process, the raw material powders may also be mixed in a pre-adjusted molar ratio. The amount of oxygen and hydrogen in the solid electrolyte material is determined by the selection of the raw material powder, the oxygen concentration in the atmosphere, the water concentration in the atmosphere and the reaction time. By operating in this way, the solid electrolyte material of the first embodiment can be obtained.
[0040] The raw material powder may also be an oxide or a halide. For example, Y 2 O 3 NH 4 Cl and LiCl.
[0041] It is considered that oxygen and hydrogen constituting the solid electrolyte material of the first embodiment are taken in from the atmosphere having a relatively high dew point described above.
[0042] (Second embodiment)
[0043] Hereinafter, the second embodiment will be described, and matters described in the first embodiment will be appropriately omitted.
[0044] The battery of the second embodiment comprises a positive electrode, a negative electrode and an electrolyte layer. The electrolyte layer is arranged between the positive electrode and the negative electrode. At least one selected from the positive electrode, the electrolyte layer and the negative electrode contains the solid electrolyte material of the first embodiment. Since the battery of the second embodiment contains the solid electrolyte material of the first embodiment, it has excellent charge and discharge characteristics.
[0045] Solid electrolyte materials with low melting points are softer than solid electrolyte materials with higher melting points. Therefore, the adhesion of the interfaces between solid electrolyte materials or the interfaces between solid electrolyte materials and other materials (such as active materials) is improved. As a result, the battery resistance is reduced, so the charge and discharge characteristics of the battery are improved. Furthermore, even if the solid electrolyte material and other materials (such as active materials) are sintered, side reactions can be suppressed.
[0046] Figure 1 A cross-sectional view showing a battery 1000 according to a second embodiment.
[0047] The battery 1000 includes a positive electrode 201 , an electrolyte layer 202 , and a negative electrode 203 .
[0048] The positive electrode 201 includes positive electrode active material particles 204 and solid electrolyte particles 100 .
[0049] The electrolyte layer 202 is disposed between the positive electrode 201 and the negative electrode 203 .
[0050] The electrolyte layer 202 contains an electrolyte material (eg, a solid electrolyte material).
[0051] The negative electrode 203 includes negative electrode active material particles 205 and solid electrolyte particles 100 .
[0052] The solid electrolyte particles 100 are particles made of the solid electrolyte material of the first embodiment, or particles containing the solid electrolyte material of the first embodiment as a main component. Here, "particles containing the solid electrolyte material of the first embodiment as a main component" refer to particles containing the solid electrolyte material of the first embodiment as the largest component.
[0053] The positive electrode 201 contains a material capable of inserting and removing metal ions (eg, lithium ions), such as a positive electrode active material (eg, positive electrode active material particles 204 ).
[0054] Examples of positive electrode active materials are lithium-containing transition metal oxides, transition metal fluorides, polyanionic materials, fluorinated polyanionic materials, transition metal sulfides, transition metal fluorides, transition metal oxysulfides or transition metal oxynitrides. Examples of lithium-containing transition metal oxides are LiNi 1-d-f Co d Alf O 2 (where 0 < d, 0 < f, and 0 < (d + f) < 1) or LiCoO 2 。
[0055] In the positive electrode 201, in order to disperse the positive electrode active material particles 204 and the solid electrolyte particles 100 well, the positive electrode active material particles 204 may also have a median particle size of 0.1 μm or more. Through this good dispersion, the charge-discharge characteristics of the battery 1000 are improved. In order to enable lithium to diffuse rapidly within the positive electrode active material particles 204, the positive electrode active material particles 204 may also have a median particle size of 100 μm or less. Due to the rapid diffusion of lithium, the battery 1000 can operate at a high output power. As described above, the positive electrode active material particles 204 may also have a median particle size of 0.1 μm to 100 μm.
[0056] In the positive electrode 201, in order to disperse the positive electrode active material particles 204 and the solid electrolyte particles 100 well, the positive electrode active material particles 204 may also have a median particle size larger than that of the solid electrolyte particles 100.
[0057] In order to improve the energy density and output power of the battery 1000, in the positive electrode 201, the ratio of the volume of the positive electrode active material particles 204 to the total volume of the positive electrode active material particles 204 and the solid electrolyte particles 100 may also be 0.30 to 0.95.
[0058] In order to improve the energy density and output power of the battery 1000, the positive electrode 201 may also have a thickness of 10 μm to 500 μm.
[0059] The electrolyte layer 202 contains an electrolyte material. This electrolyte material may also contain the solid electrolyte material of the first embodiment. The electrolyte layer 202 may also be a solid electrolyte layer.
[0060] The electrolyte layer 202 may also be composed only of the solid electrolyte material of the first embodiment. Alternatively, the electrolyte layer 202 may also be composed only of a solid electrolyte material different from the solid electrolyte material of the first embodiment.
[0061] Examples of the solid electrolyte material different from the solid electrolyte material of the first embodiment are Li 2 MgX’ 4 、Li 2 FeX’ 4 、Li(Al, Ga, In)X’ 4 、Li 3 (Al, Ga, In)X’ 6 or LiI. Wherein, X’ is at least one selected from F, Cl, Br, and I.
[0062] Hereinafter, the solid electrolyte material of the first embodiment is referred to as a first solid electrolyte material. A solid electrolyte material different from the solid electrolyte material of the first embodiment is referred to as a second solid electrolyte material.
[0063] The electrolyte layer 202 may contain not only the first solid electrolyte material but also the second solid electrolyte material. The first solid electrolyte material and the second solid electrolyte material may be uniformly dispersed. The layer formed by the first solid electrolyte material and the layer formed by the second solid electrolyte material may also be stacked along the stacking direction of the battery 1000.
[0064] In order to suppress the short circuit between the positive electrode 201 and the negative electrode 203 and to increase the output of the battery 1000 , the electrolyte layer 202 may have a thickness of 1 μm to 100 μm.
[0065] The negative electrode 203 contains a material capable of inserting and removing metal ions (eg, lithium ions), such as a negative electrode active material (eg, negative electrode active material particles 205 ).
[0066] Examples of negative electrode active materials are metal materials, carbon materials, oxides, nitrides, tin compounds or silicon compounds. The metal material may be a single metal or an alloy. Examples of metal materials are lithium metal or lithium alloys. Examples of carbon materials are natural graphite, coke, graphitized carbon, carbon fiber, spherical carbon, artificial graphite or amorphous carbon. From the viewpoint of capacity density, preferred examples of negative electrode active materials are silicon (i.e. Si), tin (i.e. Sn), silicon compounds or tin compounds.
[0067] In the negative electrode 203, in order to disperse the negative electrode active material particles 205 and the solid electrolyte particles 100 well, the negative electrode active material particles 205 may also have a median particle size of 0.1 μm or more. Through this good dispersion, the charge and discharge characteristics of the battery are improved. In order to quickly diffuse lithium in the negative electrode active material particles 205, the negative electrode active material particles 205 may also have a median particle size of 100 μm or less. Due to the rapid diffusion of lithium, the battery can operate at a high output power. As described above, the negative electrode active material particles 205 may also have a median particle size of 0.1 μm to 100 μm.
[0068] In order to disperse the negative electrode active material particles 205 and the solid electrolyte particles 100 well in the negative electrode 203 , the negative electrode active material particles 205 may have a larger median diameter than the solid electrolyte particles 100 .
[0069] To improve the energy density and output of the battery 1000 , in the negative electrode 203 , the ratio of the volume of the negative electrode active material particles 205 to the total volume of the negative electrode active material particles 205 and the volume of the solid electrolyte particles 100 may be 0.30 to 0.95.
[0070] In order to improve the energy density and output power of the battery 1000 , the negative electrode 203 may also have a thickness of 10 μm to 500 μm.
[0071] In order to improve ion conductivity, chemical stability, and electrochemical stability, at least one selected from the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a second solid electrolyte material.
[0072] As described above, the second solid electrolyte material may also be a halide solid electrolyte. Examples of halide solid electrolytes are Li 2 MgX' 4 , Li 2 FeX' 4 、Li(Al,Ga,In)X' 4 , Li 3 (Al, Ga, In)X' 6 or LiI. wherein X' is at least one selected from F, Cl, Br and I.
[0073] The second solid electrolyte material may be a sulfide solid electrolyte.
[0074] An example of a sulfide solid electrolyte is Li 2 SP 2 S 5 , Li 2 S-SiS 2 , Li 2 SB 2 S 3 , Li 2 S-GeS 2 , Li 3.25 Ge 0.25 P 0.75 S 4 or Li 10 G 2 S 12 .
[0075] The second solid electrolyte material may be an oxide solid electrolyte.
[0076] Examples of oxide solid electrolytes are:
[0077] (i)LiTi 2 (PO 4 ) 3or NASICON type solid electrolytes such as its element substitution products,
[0078] (ii) (LaLi)TiO 3 Such perovskite solid electrolytes,
[0079] (iii)Li 14 ZnGe 4 O 16 , Li 4 SiO 4 、LiGeO 4 or LISICON type solid electrolytes such as its element substitution products,
[0080] (iv)Li 7 La 3 Zr 2 O 12 or a garnet-type solid electrolyte such as an element substitution body thereof, or
[0081] (v)Li 3 PO 4 or its N-substituted form.
[0082] The second solid electrolyte material may be an organic polymer solid electrolyte.
[0083] Examples of organic polymer solid electrolytes are compounds of polymer compounds and lithium salts. The polymer compounds may also have an ethylene oxide structure. The polymer compounds having an ethylene oxide structure can contain a large amount of lithium salts, thereby further improving ion conductivity.
[0084] An example of a lithium salt is LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiSO 3 CF 3 、LiN(SO 2 CF 3 ) 2 、LiN(SO 2 C 2 F 5 ) 2 、LiN(SO 2 CF 3 )(SO 2 C 4 F 9 ) or LiC(SO 2 CF 3 ) 3One lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used.
[0085] In order to facilitate the transfer of lithium ions and improve the output characteristics of the battery 1000 , at least one selected from the positive electrode 201 , the electrolyte layer 202 , and the negative electrode 203 may contain a nonaqueous electrolyte, a gel electrolyte, or an ionic liquid.
[0086] The non-aqueous electrolyte includes a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent.
[0087] Examples of non-aqueous solvents are cyclic carbonate solvents, chain carbonate solvents, cyclic ether solvents, chain ether solvents, cyclic ester solvents, chain ester solvents or fluorine solvents. Examples of cyclic carbonate solvents are ethylene carbonate, propylene carbonate or butylene carbonate. Examples of chain carbonate solvents are dimethyl carbonate, ethyl methyl carbonate or diethyl carbonate. Examples of cyclic ether solvents are tetrahydrofuran, 1,4-dioxane or 1,3-dioxolane. Examples of chain ether solvents are 1,2-dimethoxyethane or 1,2-diethoxyethane. Examples of cyclic ester solvents are γ-butyrolactone. Examples of chain ester solvents are methyl acetate. Examples of fluorine solvents are fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, fluoroethyl methyl carbonate or fluorodimethyl carbonate.
[0088] One nonaqueous solvent selected from these may be used alone, or a mixture of two or more nonaqueous solvents selected from these may be used.
[0089] An example of a lithium salt is LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiSO 3 CF 3 、LiN(SO 2 CF 3 ) 2 、LiN(SO 2 C 2 F 5 ) 2 、LiN(SO 2 CF 3 )(SO 2 C 4 F 9 ) or LiC(SO 2 CF 3 ) 3 One lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used.
[0090] The concentration of the lithium salt is, for example, in the range of 0.5 mol / L to 2 mol / L.
[0091] As the gel electrolyte, a polymer material impregnated with a non-aqueous electrolyte solution can be used. Examples of the polymer material are polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, or a polymer having an ethylene oxide bond.
[0092] Examples of cations contained in ionic liquids are:
[0093] (i) aliphatic chain quaternary salts such as tetraalkylammonium or tetraalkylphosphonium,
[0094] (ii) an aliphatic cyclic ammonium such as pyrrolidinium, morpholinium, imidazolinium, tetrahydropyrimidinium, piperazinium or piperidinium, or
[0095] (iii) Nitrogen-containing heterocyclic aromatic cations such as pyridinium and imidazolium cations.
[0096] An example of an anion contained in an ionic liquid is PF 6 - , BF 4 - , SbF 6 - , AsF 6 - 、SO 3 CF 3 - 、N(SO 2 CF 3 ) 2 - 、N(SO 2 C 2 F 5 ) 2 - 、N(SO 2 CF 3 )(SO 2 C 4 F 9 ) - or C(SO 2 CF 3 )-3.
[0097] The ionic liquid may also contain a lithium salt.
[0098] For the purpose of improving the adhesion between particles, at least one selected from the positive electrode 201 , the electrolyte layer 202 , and the negative electrode 203 may contain a binder.
[0099] Examples of binders are polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aromatic polyamide resin, polyamide, polyimide, polyamideimide, polyacrylonitrile, polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polyhexyl acrylate, polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polyhexyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyether, polyether sulfone, hexafluoropolypropylene, styrene-butadiene rubber or carboxymethyl cellulose.
[0100] Copolymers can also be used as binders. Examples of such binders are copolymers of two or more materials selected from tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid and hexadiene. A mixture of two or more selected from these can also be used as a binder.
[0101] In order to improve electronic conductivity, at least one selected from the positive electrode 201 and the negative electrode 203 may contain a conductive auxiliary agent.
[0102] Examples of conductive additives are:
[0103] (i) Graphites such as natural graphite or artificial graphite,
[0104] (ii) Carbon blacks such as acetylene black or Ketjen black,
[0105] (iii) Conductive fibers such as carbon fibers or metal fibers,
[0106] (iv) fluorinated carbon,
[0107] (v) Metal powders such as aluminum,
[0108] (vi) Conductive whiskers such as zinc oxide or potassium titanate,
[0109] (vii) conductive metal oxides such as titanium oxide, or
[0110] (viii) Conductive polymer compounds such as polyaniline, polypyrrole or polythiophene.
[0111] For cost reduction, the conductive auxiliary agent (i) or (ii) mentioned above may be used.
[0112] Examples of the shape of the battery of the second embodiment include a coin shape, a cylindrical shape, a rectangular shape, a sheet shape, a button shape, a flat shape, or a laminated shape.
[0113] The battery of the second embodiment can be manufactured, for example, by preparing a material for forming a positive electrode, a material for forming an electrolyte layer, and a material for forming a negative electrode, and producing a stacked body in which the positive electrode, the electrolyte layer, and the negative electrode are arranged in this order by a known method.
[0114] Example
[0115] Hereinafter, the present disclosure will be described in more detail while referring to embodiments.
[0116] (Example 1)
[0117] [Production of solid electrolyte materials]
[0118] In an argon atmosphere having a dew point of -60°C or less and an oxygen concentration of 0.0001 vol% or less (hereinafter referred to as a "dry argon atmosphere"), a raw material powder was prepared according to the method of YCl 3 YCl was prepared in such a way that the molar ratio of LiCl was 1:3 3 and LiCl. These raw material powders were crushed and mixed in a mortar. The obtained mixture was calcined in an alumina crucible at 550°C for 1 hour and then crushed in a mortar. The obtained reaction product was left to stand for about 1 minute in an argon atmosphere having a dew point of -30°C and an oxygen concentration of 20.9% by volume. In this way, the solid electrolyte material of Example 1 was obtained.
[0119] [Composition analysis of solid electrolyte materials]
[0120] The contents of Li and Y per unit weight of the solid electrolyte material of Example 1 were measured by high-frequency inductively coupled plasma emission spectrometry using a high-frequency inductively coupled plasma emission spectrometry apparatus (manufactured by Thermo Fisher Scientific, iCAP7400). The content of Cl in the solid electrolyte material of Example 1 was measured by ion chromatography using an ion chromatograph (manufactured by Dionex, ICS-2000). Based on the contents of Li, Y and Cl obtained from these measurement results, the Li:Y:Cl molar ratio was calculated. As a result, the solid electrolyte material of Example 1 had a Li:Y:Cl molar ratio of 2.56:1.0:4.98.
[0121] The mass ratio of O to the whole solid electrolyte material of Example 1 was measured by non-dispersive infrared absorption method using an oxygen, nitrogen and hydrogen analyzer (manufactured by Horiba, Ltd., EMGA-930). As a result, the mass ratio of O was 0.24%. Based on this, the Y:O molar ratio was calculated. As a result, the solid electrolyte material of Example 1 had a Y:O molar ratio of 1.00:0.05.
[0122] In the composition analysis, elements having a molar ratio of 0.001% or less relative to Y are regarded as impurities.
[0123] [Infrared spectroscopy]
[0124] The solid electrolyte material of Example 1 was analyzed by total reflection measurement using an infrared spectrometer (manufactured by BRUKER, ALPHA). A diamond prism was used. The measurement results showed that in the case of protons (H + ) with oxygen bond at 3100cm -1 ~3640cm -1 The peak is detected in the region of . The surface region in the present disclosure refers to the region measured as described above. That is, the thickness of the surface region of the solid electrolyte material of the first embodiment is about 1 μm from the surface of the solid electrolyte material toward the inside. Figure 5 This is a graph showing the infrared absorption spectrum of the solid electrolyte material of Example 1.
[0125] [Determination of melting point]
[0126] In the determination of the melting point, a thermal analyzer (manufactured by TA Instruments, Q1000) was used. In a nitrogen atmosphere, the solid electrolyte material of Example 1 (about 5 mg) was measured and heated from 300°C to 530°C at a heating rate of 10K / min. An endothermic peak was observed at this time. Based on the obtained data, a two-dimensional graph was prepared by setting the horizontal axis to temperature and the vertical axis to calorific value. Two points on the graph where the solid electrolyte material neither generates heat nor absorbs heat are connected with a straight line, which is used as the baseline. Next, the intersection of the tangent at the inflection point of the endothermic peak and the baseline is set as the melting point. As a result, the melting point is 501.1°C. Figure 6 This is a graph showing the results of thermal analysis of the solid electrolyte of Example 1.
[0127] [X-ray diffraction]
[0128] In analyzing the crystal structure of the solid electrolyte material, an X-ray diffraction device (RIGAKU, MiniFlex600) was used. The X-ray diffraction pattern of the solid electrolyte material of Example 1 was measured in a dry environment with a dew point below -45°C. As an X-ray source, Cu-Kα rays (wavelength and ).
[0129] As a result of X-ray diffraction measurement, peaks were found at 15.77°, 17.96°, 31.35°, 33.67°, 40.84°, 48.75°, and 53.54°. Figure 2 This is a graph showing an X-ray diffraction pattern of the solid electrolyte material of Example 1.
[0130] [Evaluation of ionic conductivity]
[0131] Figure 3 A schematic diagram of a press forming die 300 used for evaluating the ion conductivity of a solid electrolyte material is shown. The press forming die 300 includes a punch upper portion 301, a frame 302, and a punch lower portion 303. The frame 302 is formed of insulating polycarbonate. The punch upper portion 301 and the punch lower portion 303 are both formed of electronically conductive stainless steel.
[0132] use Figure 3 The press forming die 300 shown in FIG. 1 was used to measure the ionic conductivity of the solid electrolyte material of Example 1 by the following method.
[0133] In a dry argon atmosphere, the powder 101 of the solid electrolyte material of Example 1 was filled in the press die 300. In the press die 300, a pressure of 400 MPa was applied to the solid electrolyte material of Example 1 using the punch upper part 301 and the punch lower part 303.
[0134] Under the state of applying pressure, the punch upper part 301 and the punch lower part 303 are connected to a constant potential instrument (Princeton Applied Research, Versa STAT4). The punch upper part 301 is connected to the working electrode and the potential measurement terminal. The punch lower part 303 is connected to the counter electrode and the reference electrode. The impedance of the solid electrolyte material of Example 1 is measured by electrochemical impedance measurement at room temperature.
[0135] Figure 4 This is a graph showing a Cole-Cole diagram of the impedance measurement results of the solid electrolyte material of Example 1.
[0136] exist Figure 4 The real value of the impedance at the measurement point where the absolute value of the phase of the complex impedance is the smallest is regarded as the resistance value of the solid electrolyte material to ion conduction. Figure 4 The arrow R shown in SE Using this resistance value, the ion conductivity was calculated based on the following mathematical formula (1).
[0137] σ=(R SE ×S / t) -1 (1)
[0138] Wherein, σ is the ionic conductivity. S is the contact area between the solid electrolyte material and the upper part 303 of the punch ( Figure 3 The cross-sectional area of the hollow part of the frame type 301 is equal to that of the hollow part of the frame type 301). SEis the resistance value of the solid electrolyte material in the impedance measurement. t is the thickness of the solid electrolyte material to which pressure is applied ( Figure 3 , which is equal to the thickness of the layer formed by the powder 101 of the solid electrolyte material).
[0139] The ionic conductivity of the solid electrolyte material of Example 1 measured at 25°C was 1.8×10 -4 S / cm.
[0140] [Battery production]
[0141] In a dry argon atmosphere, the solid electrolyte material of Example 1 and LiCoO as an active material were prepared in a volume ratio of 70:30. 2 These materials were mixed in an agate mortar and pestle to obtain a mixture.
[0142] In an insulating cylinder having an inner diameter of 9.5 mm, the solid electrolyte material of Example 1 (100 mg), the above-mentioned mixture (10.0 mg) and aluminum powder (14.7 mg) were stacked in sequence. A pressure of 300 MPa was applied to the stack to form the first electrode and the solid electrolyte layer. The solid electrolyte layer had a thickness of 500 μm.
[0143] Next, a metal In foil was stacked on the solid electrolyte layer. The solid electrolyte layer was sandwiched between the metal In foil and the first electrode. The metal In foil had a thickness of 200 μm. Next, a pressure of 80 MPa was applied to the metal In foil to form the second electrode.
[0144] A current collector made of stainless steel was mounted on the first electrode and the second electrode, and then a current collecting lead was mounted on the current collector. Finally, an insulating ferrule was used to block the inside of the insulating tube from the outside atmosphere, thereby sealing the inside of the tube. In this way, the battery of Example 1 was obtained.
[0145] [Charge and discharge test]
[0146] Figure 7 The initial discharge characteristics of the battery of Example 1 are shown. Figure 7 The results shown in were determined by the following method.
[0147] The battery of Example 1 was placed in a thermostatic chamber at 25°C. 2 The battery of Example 1 was charged at a current density of 84 μA / cm2 until the voltage reached 3.7 V. This current density corresponds to a 0.05C rate. 2 The battery of Example 1 was discharged at a current density of 1.9 V until the voltage reached 1.9 V.
[0148] As a result of the charge and discharge test, the battery of Example 1 had an initial discharge capacity of 632 μAh.
[0149] (Examples 2 and 3)
[0150] The solid electrolyte material of Example 2 was obtained in the same manner as in Example 1, except that the time for leaving the reaction product in the atmosphere having a dew point of -30°C was set to about 3 minutes instead of about 1 minute.
[0151] The solid electrolyte material of Example 3 was obtained in the same manner as in Example 1, except that the time for leaving the reaction product to stand in an atmosphere having a dew point of -30°C was set to about 10 minutes instead of about 1 minute.
[0152] The element ratio (molar ratio), melting point, oxygen content, infrared absorption spectrum, X-ray diffraction and ion conductivity of the solid electrolyte materials of Examples 2 and 3 were measured in the same manner as in Example 1. The measurement results are shown in Tables 1 and 2. Figure 2 This is a graph showing the X-ray diffraction patterns of the solid electrolyte materials of Examples 2 and 3. Figure 5 This is a graph showing the infrared absorption spectra of the solid electrolyte materials of Examples 2 and 3. Figure 6 This is a graph showing the results of thermal analysis of the solid electrolyte materials of Examples 2 and 3.
[0153] The solid electrolyte materials of Examples 2 and 3 were used in the same manner as in Example 1 to obtain batteries of Examples 2 and 3.
[0154] Using the batteries of Examples 2 and 3, a charge and discharge test was carried out in the same manner as in Example 1. The batteries of Examples 2 and 3 were charged and discharged in the same manner as in Example 1.
[0155] (Comparative Examples 1 and 2)
[0156] In a dry argon atmosphere, as raw material powder, YCl 3 Prepare YCl in such a way that the molar ratio of LiCl is 1:3 3 and LiCl. These raw material powders were pulverized and mixed in a mortar. The obtained mixture was calcined in an alumina crucible at 550° C. for 1 hour and then pulverized in a mortar. In this way, a solid electrolyte material of Comparative Example 1 was obtained.
[0157] The solid electrolyte material of Example 2 was obtained in the same manner as in Example 1, except that the time for leaving the reaction product to stand in an atmosphere having a dew point of -30°C was set to about 30 minutes instead of about 1 minute.
[0158] The element ratio (molar ratio), melting point, oxygen content, infrared absorption spectrum, X-ray diffraction and ion conductivity of the solid electrolyte materials of Comparative Examples 1 and 2 were measured in the same manner as in Example 1. The measurement results are shown in Tables 1 and 2. Figure 2 This is a graph showing X-ray diffraction patterns of the solid electrolyte materials of Comparative Examples 1 and 2. Figure 5 This is a graph showing infrared absorption spectra of the solid electrolyte materials of Comparative Examples 1 and 2. Figure 6 This is a graph showing the results of thermal analysis of the solid electrolyte material of Comparative Example 1.
[0159] [Table 1]
[0160]
[0161] [Table 2]
[0162]
[0163] (Inspection)
[0164] As shown in Table 1, the solid electrolyte materials of Examples 1 to 3 have lower melting points than the solid electrolyte material of Comparative Example 1. Furthermore, the solid electrolyte materials of Examples 1 to 3 have a melting point of 1×10 -4 S / cm or more. On the other hand, the solid electrolyte material of Comparative Example 2 has an ion conductivity of less than 1×10 -4 S / cm ionic conductivity.
[0165] As shown in Table 1, when the molar ratio of O to Y is greater than 0.01 and less than 0.21, the solid electrolyte material has a low melting point and high ion conductivity. It was confirmed that as the molar ratio of O to Y increases, the melting point of the solid electrolyte material decreases.
[0166] Depend on Figure 5 It was confirmed that the solid electrolyte materials of Examples 1 to 3 and Comparative Example 2 had oxygen bonded to protons. On the other hand, it was confirmed that the solid electrolyte material of Comparative Example 1 did not contain oxygen bonded to protons. That is, it is believed that the solid electrolyte material of Comparative Example 1 did not contain hydrogen. It is believed that the oxygen bonded to protons exists in the form of hydroxyl groups or hydrated water.
[0167] The batteries of Examples 1 to 3 were charged and discharged at 25°C.
[0168] Since the solid electrolyte materials of Examples 1 to 3 do not contain sulfur, they do not generate hydrogen sulfide.
[0169] As described above, the solid electrolyte material of the present disclosure is suitable for providing a battery having a low melting point and high lithium ion conductivity and capable of good charge and discharge.
[0170] Industrial Applicability
[0171] The solid electrolyte material disclosed in the present disclosure is used, for example, in an all-solid lithium ion secondary battery.
[0172] Explanation of symbols
[0173] 100 Solid Electrolyte Particles
[0174] 101 Powder of solid electrolyte material
[0175] 201 Positive electrode
[0176] 202 electrolyte layer
[0177] 203 Negative electrode
[0178] 204 Positive electrode active material particles
[0179] 205 Negative electrode active material particles
[0180] 300 Pressurized Forming Die
[0181] 301 Punch upper part
[0182] 302 frame type
[0183] 303 punch lower part
[0184] 1000 Batteries
Claims
1. A solid electrolyte material consisting of Li, Y, X, O and H, in, X is one selected from F, Cl, Br and I, The molar ratio of O to Y is greater than 0.01 and less than 0.38, In the X-ray diffraction pattern of the solid electrolyte material obtained by X-ray diffraction measurement using Cu—Kα, peaks exist in the ranges of diffraction angles 2θ of 15.2° to 16.3°, 17.4° to 18.5°, 30.8° to 31.9°, 33.1° to 34.2°, 40.3° to 41.4°, 48.1° to 49.3°, and 53.0° to 54.1°.
2. The solid electrolyte material according to claim 1, wherein X is Cl.
3. The solid electrolyte material according to claim 1 or 2, further comprising at least one selected from the group consisting of Mg, Ca, Zn, Sr, Ba, Al, Sc, Ga, Bi, La, Zr, Hf, Ta and Nb.
4. The solid electrolyte material according to claim 1 or 2, wherein In the surface region of the solid electrolyte material, O bonded to H exists.
5. The solid electrolyte material according to claim 1 or 2, wherein The molar ratio of O to Y is greater than 0.01 and less than or equal to 0.
21.
6. A battery comprising: positive electrode; negative electrode; and an electrolyte layer disposed between the positive electrode and the negative electrode, in, At least one selected from the positive electrode, the negative electrode, and the electrolyte layer contains the solid electrolyte material according to any one of claims 1 to 5.
Citation Information
Patent Citations
Method of manufacturing sulfide solid electrolyte material, sulfide solid electrolyte material, and lithium battery
JP2011129312A
Solid electrolyte material, and cell
WO2018025582A1
Solid electrolyte material, and cell
CN108701860A
Positive electrode active material and battery
CN110235288A